2021
DOI: 10.1186/s12889-021-10404-9
|View full text |Cite
|
Sign up to set email alerts
|

School-based vision screening in Quetta, Pakistan: a qualitative study of experiences of teachers and eye care providers

Abstract: Background Visual impairment in children is a significant public health problem affecting millions of children globally. Many eye problems experienced by children can be easily diagnosed and treated. We conducted a qualitative study with teachers and optometrists involved in a school-based vision screening programme in Quetta district of Pakistan to explore their experiences of training, vision screening and referrals and to identify factors impacting on the effectiveness of the programme. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(22 citation statements)
references
References 33 publications
0
22
0
Order By: Relevance
“…Training teachers to screen children in India led to an increased sense of responsibility and knowledge of eye care [ 24 ]. However, when training was too basic or limited, teachers in Pakistan reported being confused about the processes [ 84 ]. Simplified training and use of resources (e.g.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Training teachers to screen children in India led to an increased sense of responsibility and knowledge of eye care [ 24 ]. However, when training was too basic or limited, teachers in Pakistan reported being confused about the processes [ 84 ]. Simplified training and use of resources (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…In other contexts, non-financial incentives had facilitated involvement in screening and detection interventions including access to no cost eye examination for teachers [ 23 ], vision screening training among teachers leading to ‘train the trainer’ opportunities [ 24 ], and t-shirts and certificates for key informants in detecting children needing eye surgery in Tanzania [ 76 ]. Gender-based aspects of screening and detection included: localized knowledge of female community health volunteers in Nepal, and key informants in India, leading to easier identification of visually impaired children and provision of low vision aids [ 73 , 74 ]; understanding the need for gender segregated school-based vision screening in Pakistan [ 84 ]; and awareness of gender bias in Nepal, Uganda, and Malawi among female community health workers facilitated access to eye care for girls through advocacy and parent engagement [ 73 ].…”
Section: Resultsmentioning
confidence: 99%
“…Low specificity in these pilots was largely related to insufficient teacher training and supervision, poor motivation and incorrect screening procedures. 20 In other programmes that reported the sensitivity and specificity of teacher screening, results varied greatly. For instance, in Port Harcourt in Nigeria, a study of vision screening in primary schools showed a sensitivity of 53.3% and a specificity of 94.6% (PVA <6/18).…”
Section: Discussionmentioning
confidence: 99%
“…The reasons behind these variations have not yet been fully explored but most attribute these to teachers’ interests and motivations to conduct vision screening. For example, Bechange et al 20 found that in Pakistan, while some teachers were highly motivated and diligent in following the screening protocol, others could not clearly recall the procedure, reported incorrect use of the E chart and, in a few cases, delegated their screening task to older students.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation